Validating a Shortened Depression Scale (10 Item CES-D) among HIV-Positive People in British Columbia, Canada - Zhang, Wendy (Public Library of Science, 2012)
OBJECTIVE: To establish the reliability and validity of a shortened (10-item) depression scale used among HIV-positive patients enrolled in the Drug Treatment Program in British Columbia, Canada. METHODS: The 10-item CES-D (Center for Epidemiologic Studies Depression Scale) was examined among 563 participants who initiated antiretroviral therapy (ART) between August 1, 1996 and June 30, 2002. Internal consistency of the scale was measured by Cronbach’s alpha. Using the original CES-D 20 as primary criteria, comparisons were made using the Kappa statistic. Predictive accuracy of CES-D 10 was assessed by calculating sensitivity, specificity, positive predictive values and negative predictive values. Factor analysis was also performed to determine if the CES-D 10 contained the same factors of positive and negative affect found in the original development of the CES-D. RESULTS: The correlation between the original and the shortened scale is very high (Spearman correlation coefficient  = 0.97 (P<0.001). Internal consistency reliability coefficients of the CES-D 10 were satisfactory (Cronbach α = 0.88). The CES-D 10 showed comparable accuracy to the original CES-D 20 in classifying participants with depressive symptoms (Kappa = 0.82, P<0.001). Sensitivity of CES-D 10 was 91%; specificity was 92%; and positive predictive value was 92%. Factor analysis demonstrates that CES-D 10 contains the same underlying factors of positive and negative affect found in the original development of the CES-D 20. CONCLUSION: The 10-item CES-D is a comparable tool to measure depressive symptoms among HIV-positive research participants.